Nested whole-genome duplications coincide with diversification and high morphological disparity in Brassicaceae - Nora Walden (Nature Portfolio, 2020)
As one of the most successful angiosperm clades with ~4000 species, the mustard family has been diversifying into many evolutionary lineages. Here, the authors construct plastid-based phylogeny and show nested whole-genome duplications coincide with diversification and high morphological disparity.